2001
DOI: 10.1002/gcc.1136
|View full text |Cite
|
Sign up to set email alerts
|

Detection of unidentified chromosome abnormalities in human neuroblastoma by spectral karyotyping (SKY)

Abstract: Spectral karyotyping (SKY) is a novel technique based on the simultaneous hybridization of 24 fluorescently labeled chromosome painting probes. It provides a valuable addition to the investigation of many tumors that can be difficult to define by conventional banding techniques. One such tumor is neuroblastoma, which is often characterized by poor chromosome morphology and complex karyotypes. Ten primary neuroblastoma tumor samples initially analyzed by G-banding were analyzed by SKY. In 8/10 tumors, we were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…The translocations der(3)t(3; 17) and der(22)t(17;22) appeared as additional secondary translocations to der(11)t(11;17) in 2 of our patients. Similar findings were reported in a cell line (Van Roy et al, 1994 and in fresh tumors (Cohen et al, 2001). Using the CGH technique, 17q gain was detected in 60 -70% of advanced-stage NBL (Lastowska et al, 1997a;Plantaz et al, 1997;Vandesompele et al, 1998;Bown et al, 1999;Hirai et al, 1999;Breen et al, 2000;Janoueix-Lerosey et al, 2000;Plantaz et al, 2001;Vandesompele et al, 2001), similar to findings of the present series.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The translocations der(3)t(3; 17) and der(22)t(17;22) appeared as additional secondary translocations to der(11)t(11;17) in 2 of our patients. Similar findings were reported in a cell line (Van Roy et al, 1994 and in fresh tumors (Cohen et al, 2001). Using the CGH technique, 17q gain was detected in 60 -70% of advanced-stage NBL (Lastowska et al, 1997a;Plantaz et al, 1997;Vandesompele et al, 1998;Bown et al, 1999;Hirai et al, 1999;Breen et al, 2000;Janoueix-Lerosey et al, 2000;Plantaz et al, 2001;Vandesompele et al, 2001), similar to findings of the present series.…”
Section: Discussionsupporting
confidence: 93%
“…This is in contrast to the present series where this translocation was detected in only one patient. We detected der(5)t(5; 17) and der(3)t(3;17) in one patient each, similar to earlier reports in fresh tumors (Meddeb et al, 1996;Cohen et al, 2001). The translocations der(3)t(3; 17) and der(22)t(17;22) appeared as additional secondary translocations to der(11)t(11;17) in 2 of our patients.…”
Section: Discussionsupporting
confidence: 90%
“…Chromosome preparations and spectral karyotyping (SKY) analysis were acquired as previously described (30), and 25 to 75 mitoses were analyzed for each cell line.…”
Section: Cytogenetic Analysismentioning
confidence: 99%
“…1 The specific genetic alterations of NB tumors and cell lines have been explored through a panel of techniques, including Southern blot, FISH, allelotyping, chromosomal CGH (Comparative Genomic Hybridisation) and 24-color or spectral karyotyping. [2][3][4][5][6][7][8][9] Interestingly, these analyses revealed that most rearrangements were unbalanced. At the difference of balanced translocations, which exchange two chromosomal segments, giving rise to two derivative chromosomes without any gain or loss of genetic material, unbalanced translocations replace the distal segment of one chromosome by material from another chromosome.…”
Section: Introductionmentioning
confidence: 99%